Successful coach learning: Digital workbook informed by pedagogical principles - Berntsen, H.; Kristiansen, E. (International Journal of Sports Science & Coaching, 2019)
This study was based on the hypothesis that advances in cognitive science may be helpful for Coach Development Programs. We wondered: How can a learning tool such as a digital workbook that is informed by evidence-based pedagogical principles be helpful for coach development? After designing the learning material, based on the cognitive theory of multimedia learning, the digital workbook was used in a coach development program that aimed to improve coaches' need-supportiveness. Ten coaches at an elite sport school in Norway attended the program over a season, and afterwards they were asked whether the learning material had contributed to their knowledge of need-supportive skills. Thematic analysis of the interviews revealed visualization, awareness, and transfer to one`s practice as the three main themes describing the educational value of the digital workbook. The material showed the coaches how need-support can be acted out in a sport-specific context. Additionally, the learning material resulted in increased engagement and awareness through coaches' reflections, which is an important step towards integrating new material to prior knowledge and create meaningful learning. Finally, the coaches highlighted transfer of the presented learning material to their practice experiences. We conclude that cognitive science may have useful implications for the design of effective learning materials for coach development programs.